Innovative Technologies Application in Education as a Condition for Education for Society Sustainable Development - Rybalko, Lina; Lavrentieva, Elena; Voloshko, Larisa; Rozhenko, Inessa (International Journal of Engineering and Technology, 2018)
The article presents the results of the scientific research on the issue of environmental studies based on ecological-evolutionary approach. The meaning and content of the term ecological-evolutionary approach and the conceptual ideas of ecological-evolutionary approach (the idea of evolution and ecocentrism) are explained. Teaching technologies based on ecological-evolutionary approach are characterized with the approach explained as the innovative technology that, in use, will provide modernization of environmental studies within the educational aspect for the society’s sustainable development.The pedagogical experiment results are presented, confirming the technology’s effectiveness based on ecological-evolutionary approach and the implementation of ecological-evolutionary approach concepts and didactic fundament in teaching environmental subjects.